2016
DOI: 10.1007/s40520-016-0541-6
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for postoperative delirium following hip fracture repair in elderly patients: a systematic review and meta-analysis

Abstract: Related prophylaxis strategies should be implemented in elderly patients involved with above-mentioned risk factors to prevent delirium after hip surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
162
1
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(192 citation statements)
references
References 44 publications
20
162
1
9
Order By: Relevance
“…According to the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM‐5), delirium is a disturbance in attention and awareness with changes in cognition developing over a short period of time and fluctuating during the course of the day (European‐Delirium‐Association and American‐Delirium‐Society, ). Although some people with normal cognition may develop delirium when exposed to particular stress (Takacs et al ., ; Yang et al ., ; European‐Delirium‐Association and American‐Delirium‐Society, ), it generally occurs in older people with cognitive impairment, and in many cases, psychomotor disturbances of delirium include agitation (Inouye, ; Van et al ., ). Delirium occurs in about 20% of patients hospitalized in internal medicine departments and in 50% of older persons in intensive care units (Goldberg et al ., ; Noriega et al ., ; Inouye et al ., , b).…”
Section: Introductionmentioning
confidence: 99%
“…According to the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM‐5), delirium is a disturbance in attention and awareness with changes in cognition developing over a short period of time and fluctuating during the course of the day (European‐Delirium‐Association and American‐Delirium‐Society, ). Although some people with normal cognition may develop delirium when exposed to particular stress (Takacs et al ., ; Yang et al ., ; European‐Delirium‐Association and American‐Delirium‐Society, ), it generally occurs in older people with cognitive impairment, and in many cases, psychomotor disturbances of delirium include agitation (Inouye, ; Van et al ., ). Delirium occurs in about 20% of patients hospitalized in internal medicine departments and in 50% of older persons in intensive care units (Goldberg et al ., ; Noriega et al ., ; Inouye et al ., , b).…”
Section: Introductionmentioning
confidence: 99%
“…We can conclude that epidural analgesia positively affects the immune system, preventing severe postoperative immuno suppression, which is particularly due to the increase in the number of CD-3-cells, B-cells, CD4/ CD8 ratio, and partially of NK-cells. In a previous study, higher cortisol levels postoperatively were shown to be associated with a higher chance of developing POCD [4,5,7,8] . Epidural anesthesia has an important influence on the modulation of the immune response in patients who underwent major orthopedic surgery.…”
Section: Discussionmentioning
confidence: 86%
“…Postoperative cognitive dysfunction (POCD) is a major consequence of this. It is essentially "deterioration in cognition temporally associated with surgery" [4,5] , and might lead to a higher mortality rate within three post-operative months [6] . A number of studies have revealed that the inflammatory response is a key factor in the development of postoperative cognitive dysfunction (POCD) [7][8][9][10] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3 There is wide variation in reported rates of post-operative delirium. For elderly patients undergoing hip surgery, the reported incidence varies from 16% to 62% [4][5][6] with average rate of 35%. 7 Occurrence of post-operative delirium is associated with higher risk of perioperative complications like pulling out of intravenous lines, catheters, drains and dressings.…”
Section: (7)2965-67mentioning
confidence: 99%